Characterizing the circularly oriented macular pigment using spatiotemporal sensitivity to structured light entoptic phenomena - Pushin, Dmitry A.; Garrad, Davis V.; Kapahi, Connor; Silva, Andrew E.; Chahal, Pinki; Cory, David G.; Kulmaganbetov, Mukhit; Salehi, Iman; Mungalsingh, Melanie A.; Singh, Taranjit; Thompson, Benjamin; Yu, Daniel; et al. (Journal of vision (Charlottesville, Va.), 2025)
To characterize the optical density of circularly oriented macular pigment (MP) in the human retina, as a quantification of macular health, Psychophysical discrimination tests were performed on human subjects using structured light-induced entoptic phenomena. Central exclusions were used to determine the visual extents of stimuli with varying spatiotemporal frequencies. A model was developed to describe the action of circularly oriented MP, and map stimuli to perceived sizes. The experimental results provided validation for the computational model, showing good agreement between measured data and predictions with a Pearson χ2 fit statistic of 0.06. This article contains a description of a new quantification of macular health and the necessary tools for clinical development. The integration of structured light into vision science has led to the development of more selective and versatile entoptic probes of eye health that provide interpretable thresholds of structured light perception. This work develops a model that maps perceptual thresholds of entoptic phenomena to the underlying MP structure that supports its perception. We selectively characterize the circularly oriented MP optical density, rather than the total MP optical density as typically measured. The presented techniques can be applied in novel early diagnostic tests for a variety of diseases related to macular degeneration such as age-related macular degeneration, macular telangiectasia, and pathological myopia. This work both provides insights into the microstructure of the human retina and uncovers a new quantification of macular health.